Comparative study of floristic diversity along altitude in the northern slope of the central Alborz Mountains, Iran - HALIME MORADI; FARIDEH ATTAR (Biodiversitas Journal of Biological Diversity, 2019)
Moradi H, Attar F. 2019. Comparative study of floristic diversity along altitude in the northern slope of the central Alborz Mountains, Iran. Biodiversitas 20: 305-312. The Alborz is one of two main mountain chains in the north of Iran. The flora and vegetation of the sub-alpine and alpine zone of the central Alborz are less known comparing to the vegetation of lower altitudes with Hyrcanain forests. In this study, floristic composition and life-form spectra were investigated along an altitudinal transect ranging from 2000 m to the alpine and sub-nival peak of Mt. Rostam-Nisht at 4500 m. We compared the floristic diversity of the studied transect with the data obtained from an earlier studied transect in Kheyrud forest. A total of 299 taxa were found in the survey which showed high species diversity in the area. In addition, our results showed remarkable difference in life form categories between lower altitudes (Hyrcanian forests) and sub-alpine and alpine zones.